2015
DOI: 10.1002/ange.201502341
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stereoselective Intermolecular Haloetherification and Haloesterification of Allyl Amides

Abstract: An organocatalytic and highly regio-, diastereo-, and enantioselective intermolecular haloetherification and haloesterification reaction of allyl amides is reported. A variety of alkene substituents and substitution patterns are compatible with this chemistry. Notably, electronically unbiased alkene substrates exhibit exquisite regio-and diastereoselectivity for the title transformation. We also demonstrate that the same catalytic system can be used in both chlorination and bromination reactions of allyl amide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Inspired by the above success, the dibromination of alkynes was tested with present TEMPO/DBDMH system to realize the efficient synthesis of (E)-dibromoolefins. Aliphatic or aromatic alkynes, internal or terminal alkynes were all dibrominated to afford (E)-dibromoolefins in good yields (43)(44)(45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inspired by the above success, the dibromination of alkynes was tested with present TEMPO/DBDMH system to realize the efficient synthesis of (E)-dibromoolefins. Aliphatic or aromatic alkynes, internal or terminal alkynes were all dibrominated to afford (E)-dibromoolefins in good yields (43)(44)(45)(46)(47).…”
Section: Resultsmentioning
confidence: 99%
“…Encouraged by Denmark's work [36][37][38][39] , Lewis bases, which always bear a donor heteroatom, have been widely employed in activation of haleniums. Up to date, N-centered [40][41][42][43][44][45][46][47][48][49][50][51][52] , S-centered [53][54][55][56][57][58][59][60][61][62][63] , Se-centered [64][65][66][67][68][69][70] , and P-centered 71,72 Lewis bases showed high efficiency in halogenation reactions (Fig. 2a).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…[30][31][32][33][34][35][36][37][38][39][40] Particularly, due to the good convertibility of the chlorine atom and its prevalence in natural products and bioactive compounds, as well as the more reactive nature of the chloriranium ion that promotes intriguing transformations compared with other iranium ions such as brom-, iod-, and thiiranium ions, catalytic asymmetric electrophilic chlorination of alkenes has received considerable attention from chemists in the past decade. [41][42][43][44][45][46][47] For instance, Borhan et al [41][42][43][44][45] reported hydroquinidine 1,4-phthalazinediyl diether [(DHQD) 2 PHAL]-catalyzed asymmetric chlorolactonization of olefinic carboxylic acids, and developed intraand intermolecular chlorination of allyl amides with the same catalyst (Figure 1b). In addition, other groups have developed catalytic asymmetric chlorination of allyl alcohols, 33,36 homoallylic alcohols, 46 2-vinylphenylcarbamates, 47 and so on.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that this cyclization is very challenging due to the following problems: (1) Known methods for asymmetric chlorination rely on the use of secondary amides with a necessary N-H group that can act as a hydrogen-bonding donor to interact with the chiral catalyst to help control the chiral environment of the reaction. [42][43][44][45][49][50][51][52][53][54] When protected N-allyl secondary anilines, namely tertiary N-allyl anilines, are used as substrates, not only the steric hindrance on the nitrogen increases, but also the hydrogen bonding from the nitrogen-containing group disappears, which theoretically results in hard control of the enantioselectivity of the reaction. (2) Using tertiary N-allyl aniline derivatives as substrates, the electron-rich aromatic ring of the substrates easily undergoes electrophilic substitution, [55][56][57] which can retard the functionalization of the double bond to form the desired products.…”
Section: Introductionmentioning
confidence: 99%